Konsep Diri Perempuan Bercadar - Aji R Suksin; Utma Aspatria; Shela C Pello (Journal of Health and Behavioral Science, 2020)
The phenomenon of veiled women in NTT, especially in the Kupang City area itself, is an increase in wearing. This can be seen from the emergence of Islamic women's associations that have several members who wear the veil as found in Al-Wahdah Islamiyah in the city of Kupang. In social life, veiled women often get negative responses as they are considered. The purpose of this study is to find out and describe the self-concept of women who are veiled in Al-Wahdah Islamiyah, Kupang City. This study uses a qualitative approach to the type of phenomenological research. Participants in this study were five veiled women selected using the purposive sampling method. The method of data collection is done by the method of observation and in-depth interviews. Data validity test is done using the source triangulation method. The analysis technique uses the analysis technique of Miles and Huberman. The results showed that in the aspect of personal self-concept, social self concept, the ideal self concept of the five participants showed a good response. Such as dress code, behave in a social environment and have good desires for themselves and those around them.